Climate Change and Food Insecurity Dynamics in the Rural Limpopo Province of South Africa - Omotayo, Abiodun Olusola (Journal of Economics and Behavioral Studies, 2018)
In the developing nations of the world, poor gross domestic product growth has shown serious vacuum to be filled in order to achieve the sustainable development goals. In that regard, this research article intends to contribute to the sustainable development goals of the United Nation’s goal by explaining the rural food insecurity in the light of climate change dynamic in some selected rural communities of Limpopo Province, South Africa. The data employed in the study were collected from 120 randomly selected rural household heads. Data were analysed with descriptive (frequency, mean etc.) and inferential statistics (Principal component Analysis (PCA), Tobit and Probit Regression) which were properly fitted (P<0.05) for the set research objectives. Descriptive results indicate that the average age of the respondents was 52 years with 60% of the household heads being married and a mean household size of 5.The study concluded that there is climate change effect and food insecurity in the study area and therefore recommended among others that the government of South Africa should endeavour to implement a more rural focused food securityclimate change policies in order to relieve the intensity of food insecurity situations among these disadvantaged rural dwellers of the province as well as to entrench a policy of long term development of agriculture. Finally, the study emphasized that the rural farming households should be enlightened through proper extension services to carry out climate change adaptation and mitigation measures in alleviating the food insecurity situation in the rural communities of the province.